CURRENT PRINCIPLES OF TRAINING THE PROFESSIONALS IN "LABORATORY DIAGNOSIS"MAJOR IN COMPLIANCE WITH NEW STANDARDS OF MEDICAL EDUCATION - Fedoseyeva, O.V. (World of Medicine and Biology, 2015)
The article highlights the main stages and peculiarities of medical laboratory diagnostics in ZSMU particular experience of Department of Histology, Cytology and Embryology in ensuring the formation of high level specialists training, their professional competence and high ethical qualities. Two-stage system of educational process in training on laboratory diagnostics to the graduation stage fully compliant credit transfer system of education today. To generate highly qualified medical laboratory that meet the current requirements of the medical field, it is necessary to actively involve students to the laboratory of research on morphological and specialized departments, which contributes to clinical and laboratory thinking.
Keywords: laboratory diagnostics; specialists; standards